Analysis of peak expiratory flow rate and spirometry in obese and nonobese schoolchildren - Gayathri Raji; Kishore Kumar; Nisha Ganga; Meenakshi Narasimhan (Indian Journal of Respiratory Care, 2022)
Introduction: Obesity is a health condition of the collection of fat on the human body leading to increased body mass index and other health issues and has various impacts on the respiratory system, which reduces the functional capacity of the lung. It is also known that obesity in childhood is a serious health issue, leading to overweight for children. Pulmonary function test is an essential component for evaluating lung functions that shows valuable procedures for diagnosing and managing respiratory diseases. Materials and Methods: This study was conducted on school children in the age group of 11–17-year-old obese and nonobese students. Lung function was measured using the spirometry and mini-Wright's peak expiratory flow (PEF) meter to identify differences among children. Results: A total of 245 healthy boys and girls, ranging from 11 to 17 years of age, were recruited for the study. There is no statistical difference between mean spirometric values of forced vital capacity (FVC), forced expiratory volume in the first (FEV1), FEV1/FVC %, FEF 25%–75% and PEF rate for obese groups in comparison with the nonobese control group. Conclusion: The current study found that females have lower lung function than males, which is significant statistically (P < 0.03) and to overcome respiratory illness.